2010
DOI: 10.1111/j.1365-2303.2009.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Cut‐off values and significance of Oil Red O‐positive cells in bronchoalveolar lavage fluid

Abstract: Significantly increased numbers of ORO-PM were associated with various lung pathologies. However, the higher numbers observed in HIV patients require further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…A similar phenomenon has been reported to take place after intraperitoneal injection of pristane for induction of arthritis . Additionally, several human pathologies are associated with the accumulation of lipid‐laden macrophages in the airways after the macrophages had engulfed fat at distant sites in the body . However, Oil Red O staining of bronchoalveolar lavage cytospin preparations, failed to reveal more than physiological accumulation of lipid‐laden macrophages in the airways of our mice.…”
Section: Discussionsupporting
confidence: 85%
“…A similar phenomenon has been reported to take place after intraperitoneal injection of pristane for induction of arthritis . Additionally, several human pathologies are associated with the accumulation of lipid‐laden macrophages in the airways after the macrophages had engulfed fat at distant sites in the body . However, Oil Red O staining of bronchoalveolar lavage cytospin preparations, failed to reveal more than physiological accumulation of lipid‐laden macrophages in the airways of our mice.…”
Section: Discussionsupporting
confidence: 85%
“…Lipid clearance is ordinarily mediated by ATII cells and, to a lesser extent, AMs (12,13). Lipid-laden AMs, also called "foam cells," are common pathological features in animals models of lung fibrosis (14,15) and in histological specimens from patients with various chronic fibrotic lung diseases (16,17). Although foam cells are thought to be a consequence, rather than cause, of fibrotic lung disease, their very presence signifies a disruption in surfactant lipid homeostasis.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The overall data are shown in Table 2. Compared with normal values, 10–12 HIV‐infected patients BALF samples were characterized by elevated percentages of neutrophils (10% [5–25]) and ORO‐PM (40% [6–80]), as expected according to our latest study 10 . We choose to compare BALF percentages rather than absolute numbers because it has been reported that despite variability in the cell numbers between subjects, the differential cell counts represent the most consistent parameter on repeated BALF analyses 12 .…”
Section: Resultsmentioning
confidence: 91%
“…BALF was performed as previously described 10 . Aliquots were transported to the cytology laboratory at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation